Exploring the relationship amongst corporate governance mechanisms, human governance characteristics, company resources, risk disclosure, and sscm disclosure: a systematic literature review approach - Che Adenan, Nur Zharifah; Said, Roshima; Joseph, Corina (Universiti Teknologi MARA, Kedah, 2025)
Through Systematic Literature Review (SLR), this paper examines the relationship between corporate governance mechanisms, human governance characteristics, company resources, risk disclosure, and sustainable supply chain management (SSCM) disclosure. The author used ROSES to guide the review technique. Scopus, Web of Science, and Google Scholar were the main databases, and theme analysis was used. Data was synthesized from 43 papers using thematic analysis. The main themes were corporate governance mechanisms, human governance characteristics, company resources, risk disclosure, and SSCM. Thus, the analysis found 15 sub-themes. As part of corporate governance, an audit and sustainability committee, board gender diversity, and board independence greatly might improved sustainable supply chain management. The board's personality, qualities, and human governance experience affect SSCM disclosure. Companies' risk management committees and board meeting frequency might potentially affect SSCM disclosure. In addition to risk disclosure, the company's SSCM disclosure emphasizes long-term sustainability, concentrating on SDG targets 11 and 12. Corporate governance, human governance, resources, and risk disclosure help the organization succeed. This essential study covers the board's features and underlines the need for corporate management to be aware of the company's sustainability activities.